Laser synthesis and photocatalytic properties of bismuth oxyhalides nanoparticles - Korepanov, Vyacheslav E.; Reutova, Olesia А.; Kharlamova, Tamara S.; Vodyankina, Olga V.; Kulinich, Sergei A.; Svetlichnyi, Valerii A. (Nanomaterials)
Photocatalysis offers a powerful approach for water purification from toxic organics, hydrogen production, biosolids processing, and the conversion of CO2 into useful products. Further advancements in photocatalytic technologies depend on the development of novel, highly efficient catalysts and optimized synthesis methods. This study aimed to develop a laser synthesis technique for bismuth oxyhalide nanoparticles (NPs) as efficient and multifunctional photocatalysts. Laser ablation of a Bi target in a solution containing halogen salt precursors, followed by laser plasma treatment of the resulting colloid, yielded crystalline bismuth oxyhalides (BixOyXz, where X = Cl, Br, or I) NPs without the need for additional annealing. The composition, structure, morphology, and optical properties of the synthesized BixOyXz (X = Cl, Br, I) NPs were characterized using XRD analysis, electron microscopy, Raman spectroscopy, and UV-Vis spectroscopy. The effect of the halogen on the photocatalytic activity of the double oxides was investigated. The materials exhibited high photocatalytic activity in the degradation of persistent model pollutants like Rhodamine B, tetracycline, and phenol. Furthermore, the BixOyXz NPs demonstrated good efficiency and high yield in the selective oxidation of 5-hydroxymethylfurfural (5-HMF) to 2,5-furandicarboxylic acid (FDCA). The obtained results highlight the promising potential of this laser synthesis approach for producing high-performance bismuth oxyhalide photocatalysts.